Interpretation of Rehabilitation Medicine Specialty Indicators in National Report on the Services， Quality and Safety in Medical Care System - ZHOU Mouwang (康复学报)
Since 2016, Peking University Third hospital has been entrusted by the National Health Commission to undertake the work of National Center for Healthcare Quality Management in Rehabilitation Medicine. For five consecutive years, it has compiled the National Report on the Services, Quality and Safety in Medical Care System (the section of rehabilitation medicine) (hereinafter referred to as the "report"), making up the gap in relevant data of rehabilitation medicine in China. This paper aims to interpret the indicators extracted and analyzed in the report, in order to continuously improve the integrity rate and accuracy rate of rehabilitation medical service and quality and safety investigation, and promote the continuous improvement of the quality of rehabilitation medical care in China. The index is composed of two kinds of indexes: quality control index and resource consumption index. The quality control index includes structure index, process quality index and result quality index, and consists of 16 major items and 149 sub-items. The report is carried out by the National Clinical Improvement System (NCIS), and the quality, accuracy and completeness of the data report will be used as the reference for hospital evaluation and key specialty setting. In NCIS indicators, data collection can be divided into the following four forms: automatic extraction of home page, extraction of medical records, manual reading of medical records and provision of relevant departments. This paper focuses on the early rehabilitation intervention, ADL improvement rate, complications and other key indicators, structural indicators and other process quality indicators. In recent years, National Center for Healthcare Quality Management in Rehabilitation Medicine has found that whether the rehabilitation medicine department has established an information system is an important factor determining the accuracy and convenience of quality control data extraction. Rehabilitation medical treatment and quality control information system is changing from "information" to "intelligent", information management will combine with artificial intelligence natural language analysis and other emerging technologies, it can simplify and accurately the extraction process of quality control data, constantly improve the efficiency of rehabilitation medical quality control.